(untitled) (International Journal of Engineering and Computer Science, 2014)
Technology and it’s requirement comes in various ways, considering one of the aspect as the building tool to next level journey of security as Information Security with the Theme behind to make the Bio-Medical efficiently in the context of Technology , i.e. how it plays the role in making and controlling the decision system. Making a prejudice statement on the support system is lead to nest level of insecurity. But In this paper we try to give a best perdition based on information where we consider as security to the information system. Time and Technology may play the complementary aspect in the decision support based on information security, at now we can give the best to mingle of various technology where security and its related decision are most important to these days software revolution, which we call it as most important and high risky to main component if IT market for Bio- Medical. The purpose of the security plan is to provide an overview of the security requirements of the system and describe the controls that are in place or those controls that are planned for meeting the security requirements. The system security plan also delineates responsibilities and expected behavior of all the individuals who access the system. The security plan should be viewed as documentation of the structured process of planning adequate, cost-effective security protection for the system. It should reflect input from the various managers who are responsible for the system. This includes the information owners, the system operators, the system security manager, and the system administrators.